PENGARUH PROGRAM KELUARGA HARAPAN (PKH) TERHADAP KESEJAHTERAAN KELUARGA PENERIMA MANFAAT DI KECAMATAN TAMPAN KOTA PEKANBARU - Virna Museliza; Afrizal Afrizal; Risma Eliza (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2020)
This research was conducted on the members of the Family Hope Program (PKM) in the Tampan sub-district of Pekanbaru City, the purpose of this study was to find out whether the Family Hope Program (PKH) affected the welfare of the Mafaat Beneficiary Family (KPM) in Tampan District, Pekanbaru City. The method used in this study is a quantitative method applied to 95 samples used as respondents using the Slovin technique, Likert scale. The results of the study concluded that the R square of 0.345 means that the percentage of the influence of the Family Hope Program (PKH) on welfare is 34.5% while the remaining 65.5% is influenced by other variables not included in the regression model. In the regression equation Y = 9,888 + 0,487 x. Where the PKH variable (X) has a positive and significant effect on the welfare variable (Y). Hypothesis testing obtained t count of 6,200. From the t hypothesis test, the initial hypothesis of the researcher is answered, that is if t arithmetic> from t table (6,200> 1,986) then the conclusion of this study is the influence of the Family Hope Program (PKH) on the welfare of Beneficiaries (KPM) in the Tampan sub-district of Pekanbaru city.